Between code and conscience: Early-career researcher reflections on agroeconomic modelling and international research collaboration - Thom, Ferike; Beier, Felicitas; Gibson, Matthew; Sundiang, Marina; Chen, David; de Lange, Thijs; Luchtenbelt, Hermen; Tassinari, Gianmaria; Mishra, Abhijeet; Oliveira, Thais Diniz (Elsevier, 2025)
Work on the second EAT-Lancet Commission report on healthy, sustainable, and just food systems began in 2022 and is now nearing completion after 3 years and contributions from more than 100 researchers. The economic modelling undertaken for the Commission was led by the Global Economics Team of the Agricultural Model Intercomparison and Improvement Project (AgMIP)—a collaboration that brings together ten global economic models and modelling teams across different institutions. This Viewpoint, authored by ten early-career researchers (ECRs) from AgMIP who worked on the global economic modelling for the 2025 EAT-Lancet Commission, offers the first direct perspectives of ECRs in a large, international collaboration focused on the future of food systems and global economic modelling. The Viewpoint offers a forward-looking perspective on global agroeconomic modelling based on experiences during the project, starting with actionable strategies to enhance the inclusivity and sustainability of international research collaborations. The Viewpoint then identifies key limitations of the models used in the project and offers suggestions for improvement through better integration of demand, policy interventions, biophysical processes, and spatial aspects to increase accuracy and relevance. We build on the reflections on modelling to explain the central role of AgMIP-style research collaboration in the personal and professional development of ECRs. The Viewpoint concludes by reflecting on the broader futures assumed in the models and the implications of a changing political landscape on research from the perspective of ECRs.